Plano amostral para avaliação da entomofauna na cultura de soja na região de Santa Maria - Antúnez, Claudia Carolina Cabral (2014)
Knowledge of the diversity of insects present in soybean is of fundamental importance for ecological studies and pest management. Sampling is one of the bases for decision making in pest control in soybean fields. Thus, to determine the most appropriate sampling plan is to define the sampling unit, the sampling method and sample size for the quantification of enthomofauna. The study aimed to determine the sampling plan for the enthomofauna of soybean in the region of Santa Maria; to estimate the sample size for the different species of insects collected by different methods; to estimate faunal indexes and their sample sizes. Sampling of enthomofauna on soybean were conducted in three growing seasons (2010/2011, 2011/2012, 2012/2013), at the vegetative and reproductive stages in 100 fields located in São Sepé, Restinga Seca, Formigueiro, Júlio de Castilhos, Itaara, Santa Maria, São Pedro do Sul, Dilermando de Aguiar and São Gabriel. In all samples, the observation unit consisted of 30 sample points; each point insects being collected with two methods (sweep net and beat cloth). The insects were identified and further ecological measures (frequency, abundance, constancy and dominance) were performed. For each insect species collected, it was determined the appropriate number of samples for the amount of insects using the Bootstrap method. The optimal number of sampling points for each field to determine the population density varies with the species, cultivar and altitude of the place, and the value increases when population densities are close to the level of damage. The indices of frequency, abundance and constancy estimated using beat cloth are greater than the estimated by the sweep net method.